Active labor market policies in a context of high informality: The effect of PAE in Bolivia - Rafael Novella; Horacio Valencia (Inter-American Development Bank (IDB), 2019)
Information asymmetries and limited skills are two main factors affecting jobseekers' chances to access quality jobs in developing countries. This paper evaluates the effectiveness of a job intermediation and wage subsidy program in Bolivia, a country with one of the highest levels of informality in Latin-America. Using administrative and survey, we find that the program substantially increases employment, formality, and earnings. These effects are heterogeneous across different subsamples of interest. Our results suggest that Active Labor Market Policies might be an effective solution for improving access to quality jobs in the context of high informality.
Keywords: J24; J28; 330; intermediation; wage subsidy; informality; Bolivia